Virtual reality-based cognitive stimulation on people with mild to moderate dementia due to alzheimer’s disease : a randomized controlled trial - Oliveira, Jorge (2021)
The use of ecologically oriented approaches with virtual reality (VR) depicting instrumen-tal activities of daily living (IADL) is a promising approach for intervention on acquired brain inju-ries. However, results of such an approach on dementia caused by Alzheimer’s disease (AD) are still lacking. This research reports on a pilot randomized controlled trial that aims to explore the effect of cognitive stimulation reproducing several IADL in VR on people with mild to moderate dementia caused by AD. Patients are being recruited from residential care homes of Santa Casa da Misericórdia da Amadora (SCMA) which is a relevant non-profit social and healthcare provider in Portugal. This intervention lasts 2 months with a total of 10 sessions (2 sessions/week). Neuropsy-chological assessment is carried out at baseline and follow-up using established neuropsychological instruments for assessing memory, attention and executive functions. The sample consisted of 17 patients of both genders randomly assigned to the experimental and control groups. The prelimi-nary results show an improvement in the overall cognitive function in the experimental group, which suggest this approach to be effective for neurocognitive stimulation for older adults with dementia, contributing to maintain cognitive function in AD.